Application of pelvic binders by student paramedics: an observational cohort study. (2nd December 2019) - Magner, Andre; Smith, Neil; Douglin, Troy
Abstract : Background: Pelvic fractures occur in approximately 20% of all multi-system traumas and can lead to loss of life through exsanguination. Advanced Trauma Life Support (ATLS) guidelines advocate application of a pelvic binder, which is most effective when placed at the level of the greater trochanters; however, multiple studies demonstrate a high degree of misplacement. Aims: The aim of the current study was to assess the ability of UK student paramedics to locate the greater trochanters and optimally apply pelvic binders. Methods: A total of 52 student paramedics from UK universities were asked to apply a pelvic binder to a healthy volunteer using a recognised technique. The primary outcome was the location of the pelvic binder compared with an optimally applied device. Findings: n =52 with 17/49 pelvic binders incorrectly located (34%); 18% were too low and 16% were too high. Conclusion: The results demonstrate a high degree of misplacement; this represents both a challenge and an opportunity for UK higher education institutions to review the manner in which pelvic binder application is taught to the next generation of prehospital practitioners.